Deracialized Nostalgia, reracialized community, and truncated gentrification: capital and cultural flows in Richmond, Virginia and Durban, South Africa. Issue 2 (4th May 2019) - Bond, Patrick; Browder, Laura
ABSTRACT: Gentrification literature often focuses on frictions between gentrifiers (often white) and those being displaced by the process (often low-income people of color). Far less attention is paid to a revealing place-marketing strategy that papers over race politics. Businesses in gentrifying neighborhoods appeal to their customers' sense of nostalgia for a vanished way of life, while eliding racial injustices prevalent in the times they evoke. The process entails re-racialization of such sites without reference to the segregatory politics central to their creation: a mode of remaking history, without memory. In larger cities this may not be so evident, since gentrification dynamics are driven by both a sufficiently large share of the population with high disposable incomes, and a well-developed property redevelopment industry with the capacity to unleash real estate speculation. In contrast, smaller cities that have partially gentrified still exhibit incomplete erasure of the past. They provide a valuable window into this process of historical de- and re-racialization. Two such secondary cities are Richmond, Virginia, and Durban, South Africa. Both have histories of legally-enshrined racial segregation, and both are attempting, with varying degrees of success, to recast inner-city neighborhoods as cool, creative places for middle-class residents to live, consume, and produce.